Beyond the Refugee-Migrant Binary? Refugee Camp Residency Along the Myanmar-Thailand Border - T. F. Rhoden (2018)
© 2018 This is a U.S. Government work and not under copyright protection in the US; foreign copyright protection may apply Processes of mixed migration beyond the reified “refugee-migrant binary” of migration studies are an empirical reality along the Myanmar-Thailand border. Utilizing a survey of 3874 mobile individuals from Myanmar in Thailand as a case study, this paper examines the impact of past experiences of migrants on the likelihood that any one of them will reside inside a refugee camp instead of outside of one in Thailand. A dataset is constructed that specifically intersects “refugee” communities with “labor migrant” communities in order to measure the importance of factors of socioeconomic, self-identity, past persecution, and social network considerations. Though indicators like religion, ethnicity, and the fear to return are salient in the likelihood of living inside a camp, family location is the strongest single predictor variable for whether or not an individual from Myanmar will inhabit a refugee camp. Future research may benefit by researching across migrant communities normally considered disparate.